2021
DOI: 10.1007/s40368-021-00604-7
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical development in local anaesthetic training in paediatric dentistry using virtual reality simulator

Abstract: Purpose With the advancements in technology, dental pedagogy has also evolved, and new learning technologies have emerged. Virtual reality (VR) as an education tool in dentistry is underutilised. VR as an adjunct in local anaesthesia (LA) teaching in paediatric dentistry has not been investigated. The study aimed to investigate dental student's perception of dental LA VR simulation on a paediatric patient and to determine whether this can improve students learning experience. Methods Seventy-one students parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…This result agreed with Zafar et al who assessed that the Simodont simulated learning environment could be used as an adjunct in training dental students for preclinical paediatric dentistry restorative exercises [119]. Finally, Zafar et al [122] presented the use of a VR simulator tool for local anaesthesia teaching in paediatric dentistry.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This result agreed with Zafar et al who assessed that the Simodont simulated learning environment could be used as an adjunct in training dental students for preclinical paediatric dentistry restorative exercises [119]. Finally, Zafar et al [122] presented the use of a VR simulator tool for local anaesthesia teaching in paediatric dentistry.…”
Section: Discussionsupporting
confidence: 83%
“…Zafar et al found in their study that 80% of the participants disagreed that virtual reality should replace conventional simulation [119]. In another article, Zafar et al assessed that the use of VR simulation can be an additional tool that enhances students learning experience, without replacing traditional training methods [122]. According to the majority of studies, online courses were easy to access, well constructed, and understandable.…”
Section: Effectiveness and Acceptability Of The E-learning Methodsmentioning
confidence: 99%
“…However, this learning was not tailored towards paediatric patients and so the curriculum was modified after this cohort of students was surveyed for this study. The modification to the curriculum included the use of a virtual reality simulator as an adjunct to teaching (Zafar et al 2021 ). Strong practitioner confidence in LA administration is essential in preventing dental fear and anxiety in children.…”
Section: Discussionmentioning
confidence: 99%
“…The participants completed a validated post-training survey to evaluate the learning process [ 12 , 13 ]. The questionnaire aimed to determine dental students’ perceptions of experience gained through digital LA simulation compared to the traditional LA training.…”
Section: Methodsmentioning
confidence: 99%